Implementation Learning Civics for Increase Interest Learning in Elementary School Students - Zahra, Arza Ratu (International Journal of Students Education, 2024)
This research method uses a literature review conducted to discuss the application of civics learning to increase interest in learning in elementary school students. Civic education learning carried out in Elementary School has a very important role in improving the quality of education so as to produce students who are creative, critical thinkers, responsive and innovative. Civic Education (PKn) is one of the subjects that must be included in the curriculum at all levels of education, from Elementary School (SD) to college levelSchools are institutions that train students under the supervision of teachers. With the presence of Civics Education in Elementary Schools, it is expected to be able to shape the character of students and be able to help students understand and be able to carry out rights and his obligation for become inhabitant country which good, smart, skilled, and responsible. With the formation of character, students are expected to be able to overcome problem which in face. However still lots civics learning problems in elementary schools that must be resolved immediately.